Barzanji's Maulid Tradition in South River Communities as a Basis of Islamic Education (Ethnographic Study) - Salamah Salamah; Muhammad Faqih Mukaddam (Journal Analytica Islamica, 2024)
The Barzanji tradition is a tradition of reading Arabic literary works in prose that tells the history of the life of the Prophet Muhammad SAW. some are described in beautiful words, with nuances of praise for the Prophet Muhammad SAW. by Sayyid Ja'far Al-Barzanji which is still applied by the people of South Kalimantan, especially in the Hulu Sungai Selatan area. The background to the problem of this research is that in society the commemoration of the Prophet's birthday, especially Barzanji, is just a ritual, without knowing, understanding and practicing the content and meaning of the reading of Barzanji's birthday. Meanwhile, Barzanji's birthday reading contains a lot of wisdom to be used as a guide in life. The aim of this research is that the researcher wants to describe the tradition of reading Maulid Barzanji as a basis for Islamic education and its significance in the context of Islamic educational values in the Hulu Sungai Selatan community. This research uses a type of field research conducted with a qualitative ethnographic type approach and descriptive form. Data collection techniques include observation, interviews and documentation. The results of the first research explain that the Barzanji birthday tradition is the basis of Islamic education, namely the Barzanji birthday tradition not only as a routine, but as an important means in forming someone who is knowledgeable, has noble character and is obedient to Allah SWT. Second, the significance of the Barzanji birthday tradition in the context of Islamic educational values, namely strengthening ties of friendship, teaching us to always strive to be a person with noble character in accordance with our example, namely the Prophet Muhammad, and increasing our belief and love for the Prophet.